"It's something I'll do until I die": A qualitative examination into why older women in the U.S. continue screening mammography. (26th May 2022) - Brotzman, Laura E.; Shelton, Rachel C.; Austin, Jessica D.; Rodriguez, Carmen B.; Agovino, Mariangela; Moise, Nathalie; Tehranifar, Parisa
Abstract: Background: Professional guidelines in the U.S. do not recommend routine screening mammography for women ≥75 years with limited life expectancy and/or poor health. Yet, routine mammography remains widely used in older women. We examined older women's experiences, beliefs, and opinions about screening mammography in relation to aging and health. Methods: We performed thematic analysis of transcribed semi‐structured interviews with 19 women who had a recent screening visit at a mammography clinic in New York City (average age: 75 years, 63% Hispanic, 53% ≤high school education). Results: Three main themes emerged: (1) older women typically perceive mammograms as a positive, beneficial, and routine component of care; (2) participation in routine mammography is reinforced by factors at interpersonal, provider, and healthcare system levels; and (3) older women do not endorse discontinuation of screening mammography due to advancing age or poor health, but some may be receptive to reducing screening frequency. Only a few older women reported having discussed mammography cessation or the potential harms of screening with their providers. A few women reported they would insist on receiving mammography even without a provider recommendation. Conclusions: Older women's positive experiences and views, as well as multilevel and frequently automated cues toward mammography are important drivers of routine screening in older women. These findings suggest a need for synergistic patient, provider, and system level strategies to reduce mammography overuse in older women. Abstract : Older women's positive experiences and views towards mammography, as well as multilevel and frequently automated cues for mammography are important drivers of routine screening. These findings suggest a need for synergistic patient, provider, and system level strategies to reduce mammography overuse in older women.